Crescimento e produção de pirarucu, Arapaima gigas, sob diferentes densidades de estocagem em associação com búfalas leiteiras - IMBIRIBA, Emir Palmeira (Universidade Federal do Pará, 2014)
With the objective of evaluating four stock densities of pirarucu (Arapaima gigas) and to identify the one that provides the best productive performance, in length and weight gain to make possible its intensive culture, a research was carried out, during 360 days. using the densities of 5, 10, 15 and 20 fishes per 100 m2 of inundate area. Live tilapias (Tilapia nilotica), captured in a dam used for milk buffaloes management, equivalent to 6% of the pirarucu live weight, were used during four days per week. The design was completely randomized with four treatments and two replications. The data were analyzed on the basis of the application of the exponential model of growth. Mathematical expressions were obtained for each stockage density. Simple linear regression analysis were made. - However, until the first 120 days, no significant difference in weight could be observed among the four study densities. The values of the angular coefficient of the relation weight/length of pirarucu showed that its growth is of the allometric type. The maximum total size was 107.66 cm and the maximum weight was 13.43 kg, in the density of five fishes per 100 m2. However, the highest biomass, of 85.69 kg per 100 m2, was observed in the density of 10 fishes per 100 m2, suggesting that this density would be the most adequate for using in intensive systems. The excellent ponderal development of pirarucu, indicates the potential use of this species, in intensive systems associated with buffaloes.